Effectiveness of mind maps as a learning tool for medical students - Wickramasinghe, Amila; Widanapathirana, Nimali; Kuruppu, Osuka; Liyanage, Isurujith; Karunathilake, I.M. (My University, 2011)
Background The Mind Map is an expression of Radiant Thinking, the associative thought processes that proceed from or connect to a central point, and is therefore a natural function of the human mind. It is a powerful graphic technique that can be applied to improve learning and clearer thinking (Buzan & Buzan, 1993). Mind maps can be used as self-learning methods that facilitate understanding of difficult concepts. Objective The curriculum of the Faculty of Medicine, University of Colombo, Sri Lanka emphasises the need for self-directed learning and deep learning. Our objective was to evaluate the effectiveness of using mind maps as a self-learning method for the new entrants to the Faculty. Method Seventy-four new entry medical students were randomly selected and assigned to two equal groups based on their high school performance. (Mind map vs. selfselected study technique). A text on iron deficiency anaemia was selected as selfstudy material. The mind map group was given a 30-minute lesson in the technique. Both groups were exposed to the study text for a 45-minute period and were requested to answer four structured essay questions based on the study text. Results There was no significant difference between the marks of two groups. The average mark of the entire group was 34.4%. Majority (97.1%, N=34) from the mind map group felt that it is useful to summarize information and 87.9% want to study further about mind mapping. Discussion Mind map technique is not superior in newly trained for short-term learning; however majority perceived it as a useful learning tool.